Obstetric and perinatal outcomes among pregnant women after influenza vaccination and after transferred respiratory infection - M P Kostinov; A P Cherdantsev; S S Semenova; D A Tarbaeva; A A Savisko; O F Serova; S A Iozefson; N K Akhmatova; T A Kostinova; D A Praulova (IP Berlin A.V., 2015)
Objective. To examine a course of pregnancy, perinatal outcomes in pregnant women vaccinated against influenza and pregnant women who have had an acute respiratory infection (ARI). Material and methods. A comparative study of 108 pregnant women, vaccinated against influenza with vaccines Grippol® plus and Agrippal S1, and 93 unvaccinated; as well as study of 185 pregnant women (50 of whom had experienced ARI during pregnancy, 135 - not) during the 2009-2010 influenza pandemic. Were applied clinical, instrumental, immunological, statistical methods. Results. It has been proven that immunization with inactivated subunit vaccines in the second and third trimester does not impact on the clinical course of pregnancy or the intrauterine growth of fetus. Respiratory infections result in increased frequency of obstetrics pathologies (subcompensated placental insufficiency 49.6%, chronic fetal hypoxia 49.6%, gestosis 35.5% and other). Adaptation in the early neonatal period among infants born to the vaccinated women is comparable to that of infants from the placebo group. The infants born to the women having a history of ARI were 3 times or more frequent to have impaired adaptation, grade I cerebral ischemia, neonatal hyperbilirubinemia. Conclusion. Vaccination of pregnant women in the II and III trimester of gestation with immunoadjuvant and unadjuvanted subunit influenza vaccine does not affect the course of pregnancy and the early neonatal period.